Effect of nutritional education based on HBM model on anemia in Golestan girl guidance school students - Morteza .Mansourian; Zaienab shafieyan; Mostafa Qorbani; Hadi Rahimzadeh Bazraki; Abdorrahman Charkazi; Hamid Asayesh; Babak Rastgari mehr; Aziz Rezapoor (Iranian Association of Health Education and Health Promotion, 2013)
Background: Iron deficiency is one of the most important cause of anemia, the aim of this study was designed to investigate the effect of health education based on HBM model on knowledge, attitude and practice of Gorgan guidance school students about anemia. Methods: A quasi experimental study was performed on 400 students of grade three in guidance school of Gorgan which were selected via cluster and simple random sampling method. Subjects divided into intervention and control groups. Data collection was performed by a questionnaire include 51 questions based on health belief model in prevention of anemia. Analysis was performed by SPSS software and T test and chi- square tests. A p-value less than 0.05 were considered as significant. Results: The difference between knowledge and attitude and practice about anemia before intervention was not statistically significant but after intervention knowledge, attitude and practice of intervention group and control group was significantly deferent. (P <0.05). The findings show that the mean score of all dimensions (except perceived benefit and barriers) of HBM model in intervention group increase after educational intervention compare by control group. Conclusion: This study finding show that education based on HBM model can affect on students knowledge and attitude toward anemia. Therefore we suggest implementing an educational plan for student in large scale about anemia based on HBM model.